STUDI KELEMBAGAAN PERDAGANGAN SINGKONG DI KECAMATAN GUMUKMAS, KABUPATEN JEMBER - Nasir, M Abd; Wardhono, Adhitya (BISMA: Jurnal Bisnis dan Manajemen, 2018)
Abstract: Cassava is one of the commodities in the agricultural sector that has theopportunity to be cultivated and marketed on a larger scale. However, the threatwerefound that involved cassava trading institutions so the cassava distribution channelwas also constrained. This study aims to (1) identify institutional patterns managecassava farming, namely related stakeholder relations patterns, related rules andtransaction costs in managing cassava farming; (2) implement and evaluate thebusiness development model and the cassava farming business institutions. Themethod used is quantitative and qualitative in the form of existing data and tabulationof perceptual data through in-depth interview techniques. The analytical techniquesused are quantitative descriptive, qualitative approaches and Value Chain Analysis.Institutional phenomena are also examined in the cassava commodity trade chain,namely social capital, and transaction costs. The results showed that the cassavatrading chain in Gumukmas District involved 6 economic actors, namely (1) purefarmers; (2) industrial farmers; (3) Traders, (4) small industries; (5) large industries;(6) and consumers. The institutional trade in cassava is not intervened bygovernment policies or farmer groups. The Institutions produced strong social capitalthat can decreasedthe transaction costs.Keywords: Value Chain, institutional, Cassava Farmer BusinessAbstrak: Singkong merupakan salah satu komoditas di sektor pertanian yangmemiliki peluang untuk dibudidayakan dan dipasarkan dalam skala yang lebih besar.Namun, ditemukan hambatan yang melibatkan kelembagaan perdagangan singkongsehingga alur pendistribusian singkong mempunyai hambatan. Penelitian inibertujuan untuk (1) mengidentifikasi pola kelembagaan dalam pengelolaan usahatani singkong yaitu pola hubungan stakeholder terkait, aturan terkait dan biayatransaksi dalam pengelolaan usaha tani singkong; (2) melakukan implementasi danevaluasi terhadap model pengembangan usaha dan kelembagaan usaha tanisingkong. Metode yang digunakan adalah kuantitatif dan kualitatif berupa existingdata dan tabulasi data persepsi melalui teknik in depth interview. Teknik analisisyang digunakan adalah deskriptif kuantitatif, pendekatan kualitatif dan Analisis RantaiNilai (Value Chain Analysis). Fenomena kelembagaan turut dikaji dalam rantaiperdagangan komoditas singkong yaitu modal sosial dan biaya transaksi. Hasilpenelitian menunjukan bahwa rantai perdagangan singkong di KecamatanGumukmas melibatkan 6 pelaku ekonomi yaitu (1) petani murni; (2) petani industri;(3) Pedagang, (4) industri kecil; (5) industri besar; (6) konsumen akhir. Kelembagaanperdagangan singkong tidak diintervensi oleh kebijakan pemerintah maupunkelompok tani. Kelembagaan menghasilkan modal sosial yang kuat yang dapatmeminimalisir keberadaan biaya transaksi.Kata Kunci: Rantai Nilai, kelembagaan, Usaha Tani Singkong